PERFECTION OF SEX FOR THE INTERSEX (KHUNṠA) TO GET MARRIED: Maqāṣid Syarīah Perspective on Corrective Surgery - April, Muhammad; Saiin, Asrizal (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This paper sheds light on the reasons for performing corrective surgery for intersex person to get married. The data were collected through the examination of works on intersex. The results of this study reveal that Islamic law, following the maqāṣid syarīah approach, allows the intersex person to perform corrective surgery with/without the intention of marriage. The choice to conduct corrective surgery does not violate the five principles of maqāṣid syarīa: the principle of religion (ḥifẓ ad-dīn), the principle of the soul (ḥifẓ an-nafs), the principle of mind (ḥifẓ al-‘aql), the principle of descent (ḥifẓ an-nasl), and the principle of property (ḥifẓ al-māl). However, corrective surgery is limited to the people who biologically have sexual disorders and the surgery must be safe according to medical science.Artikel ini menjelaskan alasan melakukan operasi kelamin bagi orang interseks untuk menikah. Data dalam penelitian ini dikumpulkan dengan cara menelaah berbagai literatur yang membahas interseks. Hasil penelitian ini mengungkapkan bahwa berdasarkan pendekatan maqāṣid syarīah, hukum Islam membolehkan orang interseks melakukan operasi penyempurnaan kelamin, baik disertai niat untuk menikah maupun tidak terlebih dahulu. Pilihan untuk melakukan operasi penyempurnaan kelamin tidak melanggar kelima prinsip maqāṣid syarīah, yakni prinsip agama (ḥifẓ ad-dīn), prinsip jiwa (ḥifẓ an-nafs), prinsip akal (ḥifẓ al-‘aql), prinsip keturunan (ḥifẓ an-nasl), dan prinsip harta (ḥifẓ al-māl).Namun, operasi penyempurnaan kelamin hanya dapat dilakukan bagi orang yang memang benar-benar secara biologis mengalami kelainan seksual. Dan operasi yang dilakukan harus memenuhi standar ilmu kedokteran.